A Study of Tower Crane Accidents and Its Mitigation Measures from Tower Crane Operator Perspectives - Anak Balan, Esther Dau; Bin Hasmori, Muhammad Fikri (Recent Trends in Civil Engineering and Built Environment, 2022)
The construction of high-rise towers, large apartment blocks or urban buildings requires the use of tower cranes in urban areas. Loss of life, injuries and property damage are the effects that can arise if the crane handling criteria and procedures are not performed correctly. Therefore, the objectives of this study are to identify the causes of tower crane accident at site, to assess the working benefit of a tower crane operator and to suggest possible mitigation measures with related to tower crane operator welfare to reduce the tower crane accident. This study uses the quantitative method by sending structured questionnaires to safety professionals and tower crane operator as targeted respondents and descriptive analysis will be used to analyze the data. Based on the survey, the main cause of tower crane can be seen in this survey as majority of the respondents strongly agreed that it is important to wear full set of personal protection equipment when working near tower crane. Besides that, the analysis has shown that the employers should provide Employees Provident Fund (EPF) and Social Security Organization (SOCSO) to tower crane operator as their working benefits. Tower crane should be maintained and meet all safety standard as it is one of the possible mitigation measures with related to tower crane operator welfare in order to reduce tower crane accidents.